Transferring patients with Ebola by land and air: the British military experience. Issue 3 (13th May 2016) - Ewington, Ian; Nicol, E; Adam, M; Cox, A T; Green, A D
Abstract : The Ebola epidemic of 2014/2015 led to a multinational response to control the disease outbreak. Assurance for British aid workers included provision of a robust treatment pathway including repatriation back to the UK. This pathway involved the use of both land and air assets to ensure that patients were transferred quickly, and safely, to a high-level isolation unit in the UK. Following a road move in Sierra Leone, an air transportable isolator (ATI) was used to transport patients for the flight and onward transfer to the Royal Free Hospital. There are several unique factors related to managing a patient with Ebola virus disease during prolonged evacuation, including the provision of care inside an ATI. These points are considered here along with an outline of the evacuation pathway.